PRIORITAS PENGGUNAAN DANA DESA JEKAWAL KABUPATEN SRAGEN DI ERA PANDEMI COVID-19 - Arima Andhika Ayu; Royke Roberth Siahainenia; Elly Esra Kudubun (UNIVERSITAS SEBELAS MARET (UNS), 2020)
Village is the smallest administrative area in Indonesia that has an autonomous government and is given the authority to manage all government affairs (Law No. 6 of 2014) regarding villages. Jekawal Village receives village funds to prioritize, its use in increasing empowerment and dealing with unexpected disasters, such as Covid-19 pandemic. The purpose is determine the priority of village fund-spend in improving community and emergency respon’s village to Covid-19 pandemic era in 2020 fiscal year. This study used a qualitative-descriptive method. Techniques of data collections are from observation, interviews, and literature study. This research is analising to data reductions, data presentations, and found the conclusions. The research’s use structural-functional theory